Alginate oligosaccharide alleviates enterotoxigenic Escherichia coli-induced intestinal mucosal disruption in weaned pigs. Issue 12 (20th November 2018) - Wan, Jin; Zhang, Jiao; Chen, Daiwen; Yu, Bing; Mao, Xiangbing; Zheng, Ping; Yu, Jie; Huang, Zhiqing; Luo, Junqiu; Luo, Yuheng; He, Jun
Abstract : Alginate oligosaccharide (AOS) is a non-toxic, non-immunogenic, non-carcinogenic and biodegradable product generated by depolymerisation of alginate, and exhibits various salutary properties. Abstract : Alginate oligosaccharide (AOS) is a non-toxic, non-immunogenic, non-carcinogenic and biodegradable product generated by depolymerisation of alginate, and exhibits various salutary properties. The present study was designed to evaluate whether AOS supplementation could attenuate enterotoxigenic Escherichia coli (ETEC)-induced intestinal mucosal injury in weaned pigs. Twenty-four weaned pigs were randomly assigned to three treatments: (1) non-challenged control; (2) ETEC-challenged control; and (3) ETEC challenge + AOS treatment (100 mg kg −1 ). On day 12, pigs in the non-challenged group were orally infused with sterilised Luria–Bertani culture while pigs in other groups were orally infused with ETEC (2.6 × 10 11 colony-forming units). At 3 days after the challenge, all pigs were orally administeredd -xylose at 0.1 g per kg body weight and then euthanised 1 h later to obtain serum and intestinal mucosa samples. Our results showed that ETEC infection both reduced ( P < 0.05) the villus height and proportion of epithelial cells in the S phase and elevated ( P < 0.05) the percentage of total apoptotic epithelial cells in the jejunum and ileum; these deleterious effects caused by ETEC were alleviated ( P < 0.05) by supplemental AOS. Meanwhile, AOS ingestion attenuated ( P < 0.05) not only the up-regulated tumour necrosis factor receptor 1 ( TNFR1 ), cysteinyl aspartate-specific protease-3 ( caspase - 3 ), - 8 and - 9 transcriptions, as well as the enhanced caspase activities (caspase-3, -8 and -9), but also the down-regulated cyclin E1 and cyclin-dependent kinase 2 ( CDK2 ) transcriptions in jejunal and ileal mucosae, caused by the ETEC challenge. In conclusion, it is possible that the protective effects of AOS against ETEC-induced intestinal mucosal disruption in weaned pigs are associated with the restrained enterocyte death, by reducing both mitochondria-dependent and TNFR1-dependent apoptosis and the accelerated enterocyte proliferation, via enhancing the cyclin E–CDK2 complex formation.